Residual stresses effects on fatigue crack growth behavior of rib-to-deck double-sided welded joints in orthotropic steel decks - Chen, Fanghuai; Zhang, Haiping; Li, Zhaochao; Luo, Yuan; Xiao, Xinhui; Liu, Yang (Advances in structural engineering, 2024)
Rib-to-deck (RTD) innovative double-sided welded joints have the potential to enhance the fatigue resistance of orthotropic steel decks (OSDs). However, welding residual stress (WRS) has been reported to be a contributing factor to fatigue cracking of steel bridges. This paper performed fatigue crack growth of the RTD innovative double-sided welded joints of OSD considering WRS. Firstly, a thermal-mechanical sequential coupling finite element model (FEM) of the RTD double-sided welded joints was established. The WRS distribution along the direction of deck thickness was analyzed. Secondly, the FEM of the OSD segment with crack was established. The fatigue crack behavior of RTD double-sided welded joints under the combined action of vehicle load and WRS was studied. Finally, the influences of initial crack on fatigue life was analyzed. Results indicate the distribution of the transverse WRS along the direction of deck thickness is tension-compression-tension stress, which has the characteristics of the sinusoidal function. The ∆Keff value increases significantly considering WRS than without considering WRS during crack growth. WRS has a significant effect on fatigue life, and the fatigue life of the weld toe without considering WRS is about twice that of considering WRS. The crack depth and aspect ratio (a0/c0) of the initial crack affect the fatigue life of RTD double-sided welded joints.